Конструювання алгебр логарифмічного типу - Воробель, Р.А. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
Method for construction of logarithmic type algebras is presented. Theorems, which are a base for receiving explicit of expression for addition and multiplication by real scalar operations, are proved. As basic element for construction of proposed algebras is function generator of analytic form. Examples for new logarithmic type algebras are shown.